Off-Grid Emergency Tent Solutions with a Compact Solar Photovoltaic System - Mazlan, Muhammad Zaim Marwan; Mohamad, Khairul Anuar; Alias, Afishah; Nordin, Muhammad Syahmi; Wijaya, Yusmar Palapa (SHM Publisher, 2024)
In recent years, solar photovoltaic (PV) systems have seen increased utilization for powering a diverse range of applications, from residentials and buildings to off-grid installations, highlighting their growing importance in the global transition towards sustainable development using renewable energy sources. This paper proposes the development of a compact solar PV system for emergency tent systems to aid preparations and rapid response efforts during disasters and unforeseen events. The system aims to support local authorities and communities in mitigating disaster risks due to power outages. The design and implementation of an emergency tent prototype measuring 3´3 m2, with a power consumption of 0.36 kW/day using a 30 W solar PV panel and battery storage capacity of 40 Ah. The system is sufficient for powering the basic functions of dc bulbs and fans as the primary load.